2020
DOI: 10.1111/and.13796
|View full text |Cite
|
Sign up to set email alerts
|

Global perspectives on the three criteria for premature ejaculation: An observational study of ejaculatory latency, ejaculatory control and bother/distress

Abstract: Criteria for premature ejaculation (PE) were established using Western‐based samples, yet these criteria are applied worldwide for its diagnosis. This study (a) determined whether men from various world regions differ/agree on their views of ejaculation latency (ELT) and their perceptions of ejaculatory control and bother/distress, the three criteria for PE, and (b) compared PE and non‐PE men across worldwide regions on these measures. 1,065 participants were recruited via social media to respond to a survey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…The great majority of men with PE (86%) also reported the desire to last longer during partnered sex. Even so, 37% of men without PE desired this same outcome, a finding consistent with previous analyses in which estimations of the ideal EL in a sample of men were consistently longer than estimations of the typical EL, usually by around 5-7 min [21,22]. The longer ideal vs. typical EL in that study, and the general desire to last longer in the current study by both PE and non-PE men, suggest that many men, even those with normal-range ELs, see benefit to either themselves or their partners (or both) in being able to prolong sexual intercourse.…”
Section: Patterns In Men With and Without Pe And In Men With Differensupporting
confidence: 88%
See 2 more Smart Citations
“…The great majority of men with PE (86%) also reported the desire to last longer during partnered sex. Even so, 37% of men without PE desired this same outcome, a finding consistent with previous analyses in which estimations of the ideal EL in a sample of men were consistently longer than estimations of the typical EL, usually by around 5-7 min [21,22]. The longer ideal vs. typical EL in that study, and the general desire to last longer in the current study by both PE and non-PE men, suggest that many men, even those with normal-range ELs, see benefit to either themselves or their partners (or both) in being able to prolong sexual intercourse.…”
Section: Patterns In Men With and Without Pe And In Men With Differensupporting
confidence: 88%
“…This analysis was part of a more extensive survey designed to address multiple questions regarding sexual response and PE, with other analyses focusing on issues related to ejaculatory latency [21] and worldwide similarities and differences in ejaculatory latency, control, and bother/distress [22]. Only the outcome measures and group/organizing variables used in this analysis are included here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has affirmed the primacy of poor ejaculatory control as a sine qua non for a PE diagnosis. 26,27 Not only have studies indicated significant and strong differences in ejaculatory control between men diagnosed with PE (either clinically or via self-report) and men without PE, 8,17,18,27,36 but perceived control over ejaculation-in contrast with EL-has significant direct effects on both sexual satisfaction and personal distress related to the PE and has emerged as the most important explanatory variable in models predicting PE status and PE severity. Short ELs are also symptomatic of men who have difficulty delaying their ejaculatory response.…”
Section: The Respective Roles Of Pe Diagnostic Variablesmentioning
confidence: 99%
“…More inclusive analysis using the terms "bother, concern, upset, frustration, or feeling guilt" revealed reliably strong differences between PE and non-PE men, yet the overall percentage of men endorsing moderate-tovery high "bother" was still only about 70%. 8 Thus, a significant portion of men with PE symptomology appears to be "distress-free," suggesting that a role for bother/distress in defining and diagnosing PE has been far less clear than for that of the other 2 criteria, ejaculatory control and EL. Despite this ambiguous role, PE-related Patient-Reported Outcomes (PROs) 21−24 tend to place strong emphasis on the "bother/ distress" dimension of PE, with more items assessing negative consequences (although not necessarily "distress" per se) than either ejaculatory control or EL.…”
Section: Introductionmentioning
confidence: 99%